In Situ Raman Mapping of Charge Carrier Distribution in Electrolyte-Gated Carbon Nanotube Network Field-Effect Transistors - Zaumseil, Jana; Jakubka, Florian; Wang, Ming; Gannott, Florentina (Journal of Physical Chemistry C, 2013)
Solution-processed networks of purely semiconducting single-walled carbon nanotubes (s-SWNTs) can be used to create high-mobility field-effect transistors (FETs) for flexible electronics. In order to optimize network alignment and density, an understanding of carrier distribution within the FET channel is necessary. Here, we used confocal Raman microscopy to investigate charge accumulation and doping in electrolyte-gated FETs with asymmetric layers of only (7,5) nanotubes, that were selected by dispersion in poly(9,9-dioctylfluorene). The nanotube FETs exhibited hole mobilities of up to 7.5 cm2 V–1 s–1 and on/off ratios of 105. All Raman modes decreased in intensity with hole accumulation. The G′-peak and D-peak shifted linearly with negative gate voltages to higher wavenumbers. Using the G′-peak shift, the charge carrier distribution in an operating FET was mapped at different gate and source-drain voltages with high spatial resolution ( 300 nm) and over large areas. With this simple technique, we were able to visualize directly how the assignment of source and drain electrodes determined channel pinch-off and the onset of the saturation regime in FETs with nonuniform carbon nanotube distributions along the channel. In situ Raman mapping could also be applied to other semiconductors that show significant changes in their Raman spectra with doping.
EAM Import::2019-03-13